High‐throughput SNP‐based authentication of human cell lines. Issue 2 (28th June 2012) - Castro, Felipe; Dirks, Wilhelm G.; Fähnrich, Silke; Hotz‐Wagenblatt, Agnes; Pawlita, Michael; Schmitt, Markus
Abstract Use of false cell lines remains a major problem in biological research. Short tandem repeat (STR) profiling represents the gold standard technique for cell line authentication. However, mismatch repair (MMR)‐deficient cell lines are characterized by microsatellite instability, which could force allelic drifts in combination with a selective outgrowth of otherwise persisting side lines, and, thus, are likely to be misclassified by STR profiling. On the basis of the high‐throughput Luminex platform, we developed a 24‐plex single nucleotide polymorphism profiling assay, called multiplex cell authentication (MCA), for determining authentication of human cell lines. MCA was evaluated by analyzing a collection of 436 human cell lines from the German Collection of Microorganisms and Cell Cultures, previously characterized by eight‐loci STR profiling. Both assays showed a very high degree of concordance and similar average matching probabilities (∼1 × 10−8 for STR profiling and ∼1 × 10−9 for MCA). MCA enabled the detection of less than 3% of contaminating human cells. By analyzing MMR‐deficient cell lines, evidence was obtained for a higher robustness of the MCA compared to STR profiling. In conclusion, MCA could complement routine cell line authentication and replace the standard authentication STR technique in case of MSI cell lines.